Investigation of the Elements of the History of Mathematics in Secondary School Mathematics Coursebooks - Ceylan, Satı (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study investigates the use of the history of mathematics in secondary school mathematics coursebooks designed according to the new curriculum prepared in 2018 and to make alternative suggestions in which mathematics history can be used. For this purpose, four mathematics coursebooks, which were decided to be taught in schools affiliated to the Turkish Ministry of National Education for four years as of 2018, were analyzed by document analysis method, and this research attempted to determine to what extent the history of mathematics was used in these coursebooks. While making this analysis and analyzing the data, the categories proposed by Erdoğan et al. (2015) were used, including “historical notes,” “notes on usage areas of mathematics,” “applications with historical notes,” and “historical elements in students‟ extracurricular activities.” As a result of the study, it was found out that the 27 elements of the history of mathematics used in the coursebooks were mostly included at the fifth grade, in thelead-in stage, in the area of learning numbers and operations, in the form of small historical snippets about the historical development of situations other than mathematics. In light of these findings, it can be suggested that the history of mathematics is not used sufficiently in secondary school mathematics coursebooks.